2017
DOI: 10.3390/ijms18112357
|View full text |Cite
|
Sign up to set email alerts
|

miR-1224-5p Mediates Mitochondrial Damage to Affect Silica-Induced Pulmonary Fibrosis by Targeting BECN1

Abstract: Silicosis is associated with fibroblast proliferation and extracellular matrix deposition in lung tissues. The dysregulation of miR-1224-5p has been implicated in several human cancers; however, the expression and function of miR-1224-5p in silicosis is unknown. The mitochondrial dysfunctions play critical roles in some diseases, but how these processes are regulated in silicosis remains limited. Here, we explored the role of miR-1224-5p in a mouse model of silicosis. We showed that the expression of miR-1224-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…23 MiR-1224-5p also mediates mitochondrial damage to affect pulmonary fibrosis induced by silicon through targeting BECN1. 24 These data prove that miR-1224-5p has a wide range of regulatory roles in a variety of tumors and it can regulate a variety of molecular pathways to affect the occurrence and development of tumors. Furthermore, miR-1224-5p is also involved in the EMT of tumor cells.…”
Section: Introductionmentioning
confidence: 82%
“…23 MiR-1224-5p also mediates mitochondrial damage to affect pulmonary fibrosis induced by silicon through targeting BECN1. 24 These data prove that miR-1224-5p has a wide range of regulatory roles in a variety of tumors and it can regulate a variety of molecular pathways to affect the occurrence and development of tumors. Furthermore, miR-1224-5p is also involved in the EMT of tumor cells.…”
Section: Introductionmentioning
confidence: 82%
“…Their results showed that UBC-9 depletion induced a brown fat gene program in human subcutaneous adipocytes, suggesting that browning effect protects against obesityinduced metabolic diseases in humans and animal models of type 2 diabetes mellitus (T2DM; Koh et al, 2016). Wu et al (2017) reported that the expression of miRNA-1224-5p mediates mitochondria damage in lung tissues of silica-induced pulmonary fibrosis and fibroblasts exposed to TGF-b1. Suppression of miR-1224-5p hampers the progression of silica-induced fibrosis in vivo and TGF-b1-induced myofibroblast differentiation in vitro (Wu et al, 2017).…”
Section: Relationship Of Mirnas In Mitochondrial Diseases and Dysfuncmentioning
confidence: 99%
“…Wu et al (2017) reported that the expression of miRNA-1224-5p mediates mitochondria damage in lung tissues of silica-induced pulmonary fibrosis and fibroblasts exposed to TGF-b1. Suppression of miR-1224-5p hampers the progression of silica-induced fibrosis in vivo and TGF-b1-induced myofibroblast differentiation in vitro (Wu et al, 2017). Rippo et al (2014) worked on endothelial cells, a wellestablished model of replicative senescence, where the results revealed that miRNA-146a, miRNA-34a, and miRNA-181a are upregulated and conversely their target Bcl-2 is downregulated.…”
Section: Relationship Of Mirnas In Mitochondrial Diseases and Dysfuncmentioning
confidence: 99%
“…Inhibition of mitophagy activates platelet-derived growth factor receptor (PDGFR)/PI3K/AKT signaling pathway and increases ROS production, accompanied by enhanced differentiation and proliferation of myofibroblasts. Inhibitory mechanism of mitophagy involves the knockdown of PARK2 and the low expression of BECN1 induced by microRNA-1224-5p [120][121][122] . It is also reported that TGF-β induces the production of ROS and mitochondrial depolarization in pulmonary epithelial cells.…”
Section: Mitophagy and Fibrotic Diseasementioning
confidence: 99%